2014
DOI: 10.3390/molecules19044189
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus Blazei Hot Water Extract Shows Anti Quorum Sensing Activity in the Nosocomial Human Pathogen Pseudomonas Aeruginosa

Abstract: Abstract:The edible mushroom Agaricus blazei Murill is known to induce protective immunomodulatory action against a variety of infectious diseases. In the present study we report potential anti-quorum sensing properties of A. blazei hot water extract. Quorum sensing (QS) plays an important role in virulence, biofilm formation and survival of many pathogenic bacteria, including the Gram negative Pseudomonas aeruginosa, and is considered as a novel and promising target for anti-infectious agents. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…22 The effect of R. canina leaf extract on the biofilm growth of S. aureus, L. monocytogenes, P. aeruginosa, E. coli and C. albicans was tested with concentrations of the extract equal to 0.500, 0.125, 0.062 and 0.031 parts of the determined MIC values. Namely, the bacteria in biofilms can be 10 to 1000 times more tolerant to the effect of antimicrobial agents compared to their planktonic form.…”
Section: Effect On Biofilm Formation and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The effect of R. canina leaf extract on the biofilm growth of S. aureus, L. monocytogenes, P. aeruginosa, E. coli and C. albicans was tested with concentrations of the extract equal to 0.500, 0.125, 0.062 and 0.031 parts of the determined MIC values. Namely, the bacteria in biofilms can be 10 to 1000 times more tolerant to the effect of antimicrobial agents compared to their planktonic form.…”
Section: Effect On Biofilm Formation and Developmentmentioning
confidence: 99%
“…24 Once established in the patient P. aeruginosa can especially be difficult to treat. 22 Similarly, E. coli biofilms can demonstrate serious problems to human health like prostatitis, biliary tract infection as well as urinary catheter cystitis. 1 This Gram negative bacterium has low sensitivity to antibiotic treatment and has become multidrug resistant which causes an increasing public health threat.…”
Section: Effect On Biofilm Formation and Developmentmentioning
confidence: 99%
“…Furthermore, microorganism resistance is a challenge for health and food production, and the search for alternative natural antimicrobial agents continues (Ding et al, 2010;Soković et al, 2014). Synthetic fungicides, for instance, are generally effective and inexpensive, but it has been suggested that they leave residual toxicity that may have carcinogenic and teratogenic side effects (McCarroll et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium uses the ability to form a biofilm controlled by gene expression, as a resistance to the antibiotics and as a protection from the host's immune system. Anti-biofilm test applied in this study detects the inhibition of initial phase of biofilm formation (Soković et al, 2014) and according to obtained results, our samples demonstrated activity in a dosage-dependent manner. Tested essential oils in this study showed strong inhibition of the cells motility and the growth of the colonies.…”
Section: Anti-qs Activity Of Extracts and Essential Oilsmentioning
confidence: 99%